Severe multi-organ trauma complicated with SARS-CoV-2 infection in Polish child trauma signs obscuring coronaviral infection - Katarzyna Połatyńska; Łukasz Kępczyński; Marta Jankowska; Magdalena Pokorska; Piotr Grzelak; Łukasz Przysło (Pediatric Anesthesia and Critical Care Journal, 2020)
This report presents first case of severe multi-organ trauma, complicated with SARS-CoV-2 infection. The child suffered from trauma resulting from falling out of the window. Imaging revealed head trauma, areas of lung contusion and abdominal organ trauma. Co-existence of multi-organ trauma, affecting chest and lungs, obscured the characteristic for COVID-19 pneumonia appe arance.